Production of Environmentally Friendly Foam Concrete Using Waste Material: Effects of Waste Concrete Sludge and Fiber Additives - Türkel, İhsan (Gazi Universitesi Fen Bilimleri Dergisi Part C: Tasarim ve Teknoloji, 2025)
This study investigates the potential of using waste concrete sludge (CS) and polypropylene fiber (PF) to improve the physico-mechanical and thermal properties of foam concrete while promoting sustainability. Foam concrete is known for its lightweight and high thermal insulation properties, and in this research, CS is used as a partial replacement for cement at varying levels (10%, 20%, 30%), while PF is added for reinforcement. The results show that as the CS content increases, the compressive and flexural strength decrease, porosity increases, and density reduces due to the lower binding properties and higher water retention capacity of CS compared to cement. The inclusion of PF partially improves flexural strength and high-temperature resistance by reducing crack propagation, but this effect diminishes at extreme temperatures. In this context, the utilization of waste in building materials plays a crucial role. Incorporating waste into construction materials provides both environmental and economic benefits. The reuse of construction waste, such as concrete sludge, helps reduce material waste, conserve natural resources, and lower the carbon emissions associated with cement production. Particularly in concrete production, the extensive use of cement contributes to increased greenhouse gas emissions. The use of waste materials like CS can mitigate these impacts and enable the production of more environmentally friendly construction materials. In conclusion, while the use of CS in foam concrete shows environmental promise, optimizing the performance of these materials is critical to ensuring both sustainability and structural integrity. This research highlights that utilizing waste materials in the construction industry is a cost-effective and ecologically beneficial approach and underscores the need to expand the potential applications of such materials in the construction sector.